C. G. Jung’s Conception of Collective Unconscious - Buzaitė, Saulė (Problemos, 1996)
The paper presents C. G. Jung’s conception of collective unconscious. The novelty and importance of Jung’s ideas are seen in creating the more complete understanding of human phenomenological world. Phenomenon of synchronicity reveals a new understanding of the relationship between psyche and matter. Archetypal psychology is considered as new postmodern branch of Jungian psychology. The main contribution of the conception of collective unconscious consists in three aspects: psychological, philosophical and methodological. The paper gives also some critical views on C G. Jung’s conception of collective unconscious.